Asuhan Kebidanan pada Ibu Nifas Di PMB Nurwati Wilayah Kerja UPTD Puskesmas Air Tiris - Dinata , Wulan Asmaida; Nislawaty, Nislawaty (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Post-delivery is a period of recovery of the uterine organs as before the period of pregnancy. The length of the postpartum period is 6-8 weeks. Complications that often occur after childbirth are vaginal bleeding, inflammation of the puerperium, trauma during urination, damming of breast milk, meningitis, sore nipples and loss of appetite. Midwifery care for postpartum mothers should be carried out 4 times, where the first 6-8 hours after delivery, 6 days postpartum, 2 weeks postpartum, and 6 weeks postpartum. The purpose of this case is to find out the midwifery care given to postpartum mothers, with the results that Mrs. D aged 25 years P1A0 that is experiencing good changes from day to day, at 6 hours post partum the mother complains of pain in the stitches, on the second day the mother still feels pain in the stitched area and the mother says she is afraid to defecate, on the sixth day the mother does not feel pain again in the area of ??the stitches and the mother was able to defecate normally, and on the fourteenth day the mother had no more pain in the area of ??the stitches. Through the results of this study, it is hoped that postpartum mothers will continue to maintain the perineal care that has been carried out at home properly and continue to seek new information not only from health workers but can also be done from the internet or from other sources. Thus the care provided to these patients is carried out properly.